INSTITUTIONALIZATION OF ACCRUAL ACCOUNTING IN LOCAL GOVERNMENT MALANG - Puspita, Wulan Dri (Accounting Department,, 2017)
This research aim to understand the application of accrual accounting in Malang viewed from their organizational change using New Institutional Sociology's perspective. This research is qualitative research with case study as the background to understand the context of accrual adoption. The results indicated about isomorphism while implementing accrual accounting in Malang, such as: coercive through pressure from the central government using their regulation, mimetic through learning from external parties that more experience, and normative through the role of professional actors. Decoupling behavior also emerged as a response of changes to develop accounting standards based on accrual.Keys: Accrual Accounting, New Institutional Sociology, Organizational change, Isomorphism